The Effect of Problem-Based Learning Model on Students’ Writing Ability in Recount Texts at Grade Ten of State Senior High School 7 Tanjungbalai in the 2025/2026 Academic Year - Novi Malinda; Yen Aryni (Universitas Islam Sumatera Utara, 2026)
This study investigated the effect of the Problem-Based Learning (PBL) model on students’ ability in writing recount texts at State Senior High School 7 Tanjungbalai during the 2025/2026 academic year. The research was motivated by students’ difficulties in organizing ideas, applying appropriate grammatical structures, and developing coherent recount texts through conventional instructional methods. The study addressed whether the implementation of the PBL model significantly improved students’ writing ability compared to traditional teaching strategies. A quantitative experimental design was employed involving 68 tenth-grade students, consisting of 34 students in the experimental group and 34 students in the control group. Data were collected through pre-test and post-test writing assessments and analyzed using the t-test formula. The findings revealed that the experimental group demonstrated a substantial improvement, with the mean score increasing from 62.2 in the pre-test to 81.5 in the post-test, while the control group improved from 57.6 to 66.8. Statistical analysis showed that the t-observed value (11.14) exceeded the t-table value (1.997) at the significance level of 0.05 with 66 degrees of freedom. The study concludes that the Problem-Based Learning model has a significant positive effect on students’ ability in writing recount texts.